Utilization and Management of Demersal Fisheries in West Sumbawa Regency, West Nusa Tenggara Province - Nunik Cokrowati; Haerul Jibriel; Baiq Raihanun; Erwansyah Erwansyah; Arzianingsih Arzianingsih; Rinto Basuki; Sri Ahdyanti; Budianto Budianto; Muhammad Junaidi; Nanda Diniarti; Dewi Putri Lestari; Laily Fitriani Mulyani (Jurnal Natur Indonesia, 2023)
Kabupaten Sumbawa Barat sea (KSB) is included in WPPNRI 573, including the Sawu Sea area, Indian Ocean waters, western Timor Sea, southern Java waters, and southern West Nusa Tenggara (KKP, 2014). The potential for demersal fish is in second place after pelagic fish with a total production of 103,501 tons from the potential fishery resources of WPPNRI 573 of 929,330 tons. An increase in catches that exceeds the sustainable potential value will reduce the catches of the next cycle and even have the potential for the extinction of fishery resources. So it must be overcome by making arrangements for the fishing effort to match the carrying capacity of the resource. The purpose of this study was to determine the sustainable potential of demersal fisheries and their level of utilization in West Sumbawa Regency. The methods used in the preparation of this study are field surveys and descriptive methods. The data obtained were analyzed statistically and descriptively, estimating fish stocks using the Schaefer Surplus Production Model. The results showed that the relationship between effort and CPUE obtained a linear equation y=8809-4.425x with R=0.024 which means that there is no relationship between fishing gear and catch. The catch is influenced by external factors such as seasonality and oceanographic conditions. The optimum effort value is 19,489.91 trips per year and the maximum sustainable catch is 8,584,332 kg per year. The last year's utilization rate value was 0.01% with an effort level value of 0.01%. The utilization rate is still relatively low, namely less than 100%.